A study of the strategic environment of an R&D section within a larger organisation - Falkingham, Leslie T. (Cranfield University, 2001)
This work addresses the problem of how an R&D section should decide on a strategy to guide its work when there is no strategic direction supplied from above by the company. The work includes a participant observer case study carried out over five years in a single R&D section, an analysis of research papers on the subject of management of section level R&D, and a review of textbooks on strategy, management and organisational behaviour. From the case study it was concluded that the company itself formed the strategic environment which the strategy of the R&D section had to address, and that the section’s strategic environment was chaotic in the mathematical sense. From the review of management textbooks it was concluded that standard theories do not give usable guidelines for the manager in this situation. A theory was developed that R&D strategy can be thought about in four distinctly different ways. Publications concentrate on two of these, while the case study and surveys of practising managers revealed that the other two were more pertinent in practice. The analysis of research papers was carried out using a newly developed technique, which showed that this body of literature is in a pre-paradigm state. The new technique was also used to show that the four different ways of thinking about R&D are present in the papers. The new literature analysis technique and the theory that R&D strategy can be thought about in four different way were tested by means of questionnaires filled in by authors of papers and by groups of R&D practitioners.
Keywords: Research and development